The story of building healthful houses in East Nusa Tenggara, Indonesia - Semiarto Aji Purwanto; Indraini Hapsari
Abstract While the State plays an important role in actively transforming communities into conditions considered as 'developed', at the micro level there are some traditional features which persist. This short ethnographic observation carried out among the Dawan in the village of Oinlasi, South Amanatun, East Nusa Tenggara, revealed that the ume kbubu, a Timorese traditional house style, has experienced some changes as a consequence of the introduction of the Ministry of Health's 'healthful housing' program around fifty years ago. It was found that this program, along with other development programs, has changed the traditional life of the communities in the village. However, the researchers also witnessed that the communities were responding to these changes in various ways. The traditional houses were, in some cases, built with modern materials, equipped with electricity, and used only as a kitchen, while the family lived in modern healthful housing nearby. It is concluded that, although the idea of healthful houses is accepted by the community, their traditional house persists.